Building and Developing the Academic Leadership Pipeline - J. Micheal Crafton; Amber M. K. Smallwood; Elroi J. Windsor (Academic Chairpersons Conference Proceedings, 2020)
Presenters and participants will explore the need for and opportunities to build, support, and sustain a scaffolded infrastructure to enhance academic leadership knowledge and skills while developing a pipeline of academic leadership talent within the university.
Keywords: academic leadership; leadership pipeline; talent development; succession management